Performance and discriminatory capacity of Nutri-Score in branded foods in Greece - Vlassopoulos, Antonis; Katidi, Alexandra; Kapsokefalou, Maria (Frontiers in Nutrition, 2022)
Background: The harmonization of front-of-pack nutritional declaration is in the heart of food & nutrition policy discussions in Europe. The Nutri-Score system has been proposed by many countries as a potential candidate but its suitability for use across Europe is still under consideration. The current study aimed to evaluate the performance and discriminatory capacity of Nutri-Score in Greece and to test its alignment with the national food-based dietary guidelines. Methods: Data on the energy, saturated fat, total sugars, sodium, protein and fiber content per 100g or ml were extracted for all foods available (n=4002) in the Greek branded food composition database HelTH. Each food content in fruits, vegetables, pulses, nuts and oils was manually estimated from the ingredients list. The Nutri-Score algorithm was used both as a continuous (FSAm-NPS Score) and a categorical variable (Grades (A)-(E)). Results: The average FSAm-NPS Score in Greece was 8.52 ± 9.4. More than half of the solid foods (53.8%) were graded from (A) to (C), while most beverages (59.2%) were graded (E). More than 50% of food categories were populated with foods in all Nutri-Score grades, indicative of a good discriminatory capacity. The system scores favourably vegetables, pulses and low-fat dairy products and unfavourablly sweets and processed meats showing in this way good alignment with the national guidelines. Eggs and seafood scored preferably compared to meat products. Animal fats received less favourable scores and so did cereal products that were highly processed. Discussion: Nutri-Score showed good capacity to inform consumers towards better food choices in line with the national guidelines. It showed a potential to guide consumers and manufacturers towards less energy dense and more nutrient dense options and highlighted areas of improvement in the food supply.